ナンキョク ショウワキチ ダイ10 キョジュウトウ ニ シヨウ サレタ コウザイ オヨビ トマク ノ ケイネン ヘンカ - 近藤, 照夫; コンドウ, テル; 平山, 善吉; ヒラヤマ, ゼンキチ; Kondo, Teruo; Hirayama, Zenkichi (2002)
P(論文) 南極昭和基地で約29年間使用された第10居住棟から採取された鋼材および塗装亜鉛めっき鋼板の経年変化を調査した結果、以下のようなことが把握された。 鋼材の腐食生成物は一般的な大気中で生じるα型とγ型のオキシ水酸化鉄および鉱物成分であるCaAl2SiO8が検出され、特に塩化物イオンが多い環境で生じるβ型オキシ水酸化鉄は検出されていない。また、屋根、壁および床に適用されていた塗装亜鉛めっき鋼板は、工場で焼付け塗装されたメラミン硬化形アクリル樹脂塗料の上に、常温乾燥形塗料である酸化重合形油変性アルキド樹脂塗料を用いて、2～3層の塗り重ねが施されていると推定できる。 沿岸部に建設されたにもかかわらず、年間の気温や相対温度が低い南極においては、金属の腐食反応や塗膜の劣化反応が抑制されていると判断できる。 The results of an investigation of steel and paint coated galvanized steel sheet used in the old living hut built in 1969 at Syowa Station, Antarctica are described. The steel corrosion products consist of α-FeOOH and γ-FeOOH, which are produced in air, and the mineral component CaAl2SiO8. However, β- FeOOH, which can be produced in air and includes a great amount of chloride ion, is not detected. In addition it is speculated that the paint coated galvanized steel sheets applied to roofs, walls and floors of the building are coated by two or three-layers of oxidation-cured melamine. It is judged that metallic corrosion and coating deterioration reactions are inhibited in Antarctica where air temperature and relative humidity are low all year, even though the buildings are located on the seashore. departmental bulletin paper